A THE CONTENT OF PREPARING STUDENTS FOR MANAGEMENT IN PEDAGOGICAL ACTIVITIES AND THE IMPORTANCE OF AN INNOVATIVE APPROACH: THE CONTENT OF PREPARING STUDENTS FOR MANAGEMENT IN PEDAGOGICAL ACTIVITIES AND THE IMPORTANCE OF AN INNOVATIVE APPROACH - Tojibaeva, Nazokatkhon (Журнал иностранных языков и лингвистики, 2022)
The article discusses the development of a seminar-training program for the formation of strategic planning, management and leadership skills of students in higher education institutions, the most effective technologies based on scientific and technological achievements and the preferred and science-based tools of teachers. thought.